Investigation of Interfacial Characteristics as a Key Aspect of the Justification of the Reagent Regime for Coal Flotation - Aleksandrova, Tatyana N.; Kuznetsov, Valentin V.; Prokhorova, Evgeniya O. (Minerals (Basel), 2025)
This work presents a comprehensive approach for the justification of the reagent regime of coal flotation by investigating the interfacial characteristics of flotation phases with various techniques. For the energy characterization of the surface processes in flotation systems, a method of establishing the components of the specific surface Gibbs energy on the basis of a numerical estimation of surface free energy change during the adsorption of flotation reagents using the Owens–Wendt–Rabel–Kaelble technique was proposed. Using the developed approach, the features of the kinetics of n-hexane sorption on the surface of coal samples were established. The substantiation of differences in the potential mechanisms of the fixation of strictly apolar and aromatic reagents is based on the results of the quantum–chemical modeling of the states of the coal–adsorbate system using the software packages Avogadro and Orca. The simulation shows the possibility of aliphatic and aromatic reagents’ synergetic effects on coal surface hydrophobization. Based on the results of quantum–chemical modeling, it was found that for the physical adsorption of an oxyethylated nonyl-phenol molecule on a molecular fragment of the coal surface, according to the Weiser model, the decrease in the energy of the system was 0.05562 eV, which indicates the high thermodynamic probability of the physical sorption of this compound. The parameters of the Langmuir monomolecular model for the sorption of oxyethylated nonyl-phenol on the surface of the studied coal samples were established. The criterion characterizing the interphase phenomena in the flotation system based on the results of potentiometric studies of the interfacial characteristics, Ef, was proposed. It was found that for the studied values of the flow rate of oxyethylated nonyl-phenol, the highest value of Ef was achieved when the value of the sorption of the reagent equaled 63.99% of the limiting sorption capacity. The performance of the proposed reagents for coal flotation was confirmed by flotation tests.